Epidemiology and survival of non-malignant and malignant meningiomas in middle-aged females, 2004-2018 - Cao, Junguo; Yan, Weijia; Hong, Xinyu; Yan, Hong (Frontiers in Oncology, 2023)
The incidence of meningioma is disparate to sex: meningiomas are more common in women than in men, especially in middle-aged women. Understanding the epidemiology and survival of middle-aged women with meningiomas would help estimate their public health impacts and optimize risk stratification. Data on middle-aged (35–54 years) female patients with meningiomas between 2004 and 2018 were obtained from the SEER database. Age-adjusted incidence rates per 100 000 population-years were calculated. Kaplan-Meier and multivariate Cox proportional hazard models were utilized in the overall survival (OS) analysis. Data from 18302 female patients with meningioma were analyzed. The distribution of patients increased with age. Most patients were White and non-Hispanic, according to race and ethnicity, respectively. Over the past 15 years, non-malignant meningiomas have shown an increasing trend; however, malignant meningiomas have shown an opposite trend. Older age, Black population, and large non-malignant meningiomas tend to have worse prognoses. Surgical resection improves OS, and the extent of resection is a critical prognostic factor. This study observed an increase in non-malignant meningiomas and a decrease in the incidence of malignant meningiomas in middle-aged females. The prognosis deteriorated with age, in Black people, and with large tumor size. Additionally, the extent of tumor excision was found to be a significant prognostic factor.